Measuring Agriculture Research and Development Return on Investment: Relevance for Florida - Julia Delaney Ulrich; Suzanne Thornsbury; Christa Court; Amanda B. Heinzmann (EDIS)
This publication describes why science and research are critical to the future success of agriculture. It provides an overview of challenges to evaluating outcomes of research investments and some common approaches to measuring returns. The authors summarize emerging federal science and research priorities significant for Florida agriculture. The publication is intended as a helpful reference for Florida producers, taxpayers, and state government agencies. It is part of a series that examines federal policies relevant to specialty crops.